Interstate aspects of national security in the context of foreign policy of Kazakhstan and Iran: comparative analysis - Tulubayeva, А.У.; Turhanova, А.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The article examines the problems of ensuring national security at the domestic and regional levels of Kazakhstan and Iran, the normative documents of the two states on this issue, provides a comparative analysis of the systems of ensuring national security of the two countries, measures to combat modern threats such as radical extremism, terrorism, interethnic and interfaith conflicts, and shows the level of cooperation between our state and the Islamic republic on issues identified by the topic of the article. The authors of the article briefly analyze the foreign policy activity of the Republic of Kazakhstan and the Islamic Republic of Iran in terms of an adequate response to modern national security challenges.